Founder influences on the development of organizations: A comparison between founder and non‐founder managed Russian firms - Shirokova, Russia V.; Knatko, Dmitri (Journal of Business Economics and Management, 2008)
The paper deals with the problem of founders’ impact on the process of organizational development and performance. The goal of the research is to provide a comparative analysis of activity in founder‐run and non‐founder‐run Russian firms. In order to run this analysis 224 companies created from scratch by Russian entrepreneurs in the period of years from 1992 to 1998 were studied. Statistical analyses were performed on two independent samples of companies, namely 162 companies managed by the founders and 62 companies that were run by hired professional managers. As a result of the analysis, statistical differences were found in relation to the criteria of number of employees and hierarchical levels; firms managed by founders usually have less staff and fewer hierarchical levels than the non‐founder companies. Nevertheless the dynamics in sales of the two samples of founder and non‐founder companies during the last 3 years were quite similar.First published online: 14 Oct 2010